A Treatise on Probability - Keynes, John Maynard (London: Macmillan & Co. ltd., 1957)
This book is divided into five parts: 1) fundamental ideas; 2) fundamental theorems; 3) induction and analogy; 4) some philosophical applications of probability; and 5) the foundations of statistical inference.
Includes bibliographical references and index.
ne 23/03/2018
Loan
Keywords: Probabilities